Chemical ribosylation of 5-substituted 1, 2, 4-triazole-3-carboxylates. (3rd August 2019) - Prutkov, Alexander N.; Chudinov, Mikhail V.; Matveev, Andrey V.; Grebenkina, Lyubov E.; Berezovskaya, Yulia V.
Abstract: The chemical ribosylation pathways of 5-substituted-1, 2, 4-triazole-3-carboxylates are discussed. For the products of the chemical synthesis of the 3(5)-alkyl- or 3(5)-aryl-substituted ribavirin analogues the anomer configuration and isomer composition were determined.